Effect of mixture of diazinon and benzo[a]pyrene in Glutathione S-transferase of Nile tilapia - Da Silva, Daniele Caetano [UNESP]; Trídico, Camila Pereira [UNESP]; Serrano, Lenard [UNESP]; De Almeida, Eduardo Alves [UNESP] (Centro Universitario Sao Camilo - Sao Paulo, 2014)
Currently, with the growing contamination of aquatic ecosystems, many compounds, such as pesticides and hydrocarbons, are improperly released into rivers and lakes. Studies about the exposure of single pollutants causing biochemical variations are abundant in the literature. However, there are few studies focused on the biological effects of complex mixtures. The aim of this investigation was to evaluate whether mixture diazinon and benzo[a]pyrene can affect the biochemical activities of classic biomarkers such as acetylcholinesterase (AChE), carboxylesterase (CbE), catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferase (GST) in Nile tilapia and compare the effects on enzymatic systems of the exposure to a mixture of compounds and the effects observed when they are exposed separately. We measured the activity of enzymes in gills and liver of Nile Tilapia (Oreochromis niloticus) after 2 and 7 days of exposure to Diazinon (0.5 mg/L) and benzo[a]pyrene (1.0 mg/L) individually and in mixture. The results showed that in the mixture group after 7 days of exposure, the benzo[a]pyrene increased the inhibitory action of Diazinon in GST enzyme activity, in liver tissue. This indicates that the toxicity of the interactions between pesticide and polycyclic aromatic hydrocarbon may show synergistic effect. These results suggest the importance of studies with mixture of compounds, because these data will help to understand the results obtained in field studies, such as those from environmental monitoring.
Keywords: Benzo[a]pyrene; Biomarkers; Cichlids; Diazinon; Pharmacological